Pengaruh Arang Sekam Dan Dosis Pupuk NPK Terhadap Pertumbuhan Dan Hasil Tanaman Jagung (Zea mays L.).: Arang Sekam Dan Dosis Pupuk NPK Terhadap Pertumbuhan Dan Hasil Tanaman Jagung (Zea mays L.). - Sri Indriyanti; Priyono Priyono; Saiful Bahri (Innofarm:Jurnal Inovasi Pertanian, 2022)
This study entitled The Effect of husk Charcoal and Dosage of NPK Fertilizer n Growth and Yield of Corn plan (Zea mays L.), this study aims to analyze the effect of husk charcoal and NPK fertilizer dosage on. Growth and yield of maize, which was carried out from August to November 2021. The research was conducted in Mendalan, Jipangan, Banyudono, Boyolali with an altitude of 158 meters above sea level. The type of soil used was regosol soil. This study used the Completely Randomized Block Design (CRBD) method which was arranged in a factorial manner consisting of 10 treatments, each treatment repeated 3 times. The fertilizers used were husk charcoal and NPK fertilizer. The data from this study were analyzed by using the LSD (Least Significant Difference) test at a level of 5%. Parameters observed included plant height, number of leaves, number of cobs, weight of cobs with cob, weight of cobs without husks, weight of wet stover, dry weight of stove. The results showed that 1. In the growth phase, the treatment of husk charcoal and dose of NPK fertilizer had an effect on plant height and dry weight of stover. Treatment without husk charcoal 2 kg/tan and dose of NPK fertilizer 1.16 g/plant (A0N3), on plant height produces an average of 266.37 cm and dry stover weight of husk charcoal 2 g/plant and dose of NPK fertilizer 1.23 g/plant (A1N4) with an average of 434.33 g/plant. While on the number of leaves, the weight of wet stover slightly affected (tendency) which gave different results. The number of leaves without charcoal and the dose of NPK fertilizer was 1.16 g/plant (A0N3) with the highest yield of 15.33 strands and the weight of wet husk bnbbbcharcoal was 2 g/plant and the dose of NPK fertilizer was 0 g/plant (A1N0) with an average of - the highest average is 984.77 grams. 2. In harvest yields, the treatment of husk charcoal and the dose of NPK fertilizer had no effect on the treatment without husk charcoal and the dose of NPK fertilizer was 1.01 g/plant (A0N1). husk charcoal husks of 2 kg/plant and a dose of NPK fertilizer 0 g/plant yielded an average of 31.72 grams and the weight of cobs without husks was treated without husk charcoal and a dose of NPK fertilizer of 1.16 g/plant (A0N3) produced an average of 20 ,26 grams. Keywords : Husk Charcoal , NPK, Growth, Yield, Corn